On the nature of hydrostatic equilibrium in galaxy clusters - Biffi, Verónica (2016)
In this paper we investigate the level of hydrostatic equilibrium (HE) in the intra-cluster medium of simu-lated galaxy clusters, extracted from state-of-the-art cosmological hydrodynamical simulations performed withthe Smoothed-Particle-Hydrodynamic code GADGET-3. These simulations include several physical processes,among which stellar and AGN feedback, and have been performed with an improved version of the code thatallows for a better description of hydrodynamical instabilities and gas mixing processes. Evaluating the radialbalance between the gravitational and hydrodynamical forces, via the gas accelerations generated, we effectivelyexamine the level of HE in every object of the sample, its dependence on the radial distance from the center and onthe classification of the cluster in terms of either cool-coreness or dynamical state. We find an average deviation of10?20% out to the virial radius, with no evident distinction between cool-core and non-cool-core clusters. Instead,we observe a clear separation between regular and disturbed systems, with a more significant deviation from HEfor the disturbed objects. The investigation of the bias between the hydrostatic estimate and the total gravitatingmass indicates that, on average, this traces very well the deviation from HE, even though individual cases showa more complex picture. Typically, in the radial ranges where mass bias and deviation from HE are substantiallydifferent, the gas is characterized by a significant amount of random motions ( 30 per cent), relative to thermalones. As a general result, the HE-deviation and mass bias, at given interesting distance from the cluster center, arenot very sensitive to the temperature inhomogeneities in the gas.